(untitled) (Journal of Libya for geographical studies, 2024)
This study, entitled “The Movement of Tankers and Petroleum Products at the Brega Pier in the Bay of Tobruk,” is one of the studies concerned with topics of transportation geography. The problem of the study lies in the question: What is the volume of commercial activity at the Brega Pier in the Bay of Tobruk? Therefore, the study aimed to evaluate the level of movement of tankers and petroleum products on the dock and to identify the economic and political factors affecting this movement, as well as to identify the types of unloaded and shipped petroleum products. The historical approach, the descriptive approach and the analytical approach were all used in preparing this study. The study reached the following conclusions: Many results, the most important of which is that the Brega pier is located within the Gulf of Tobruk, which is classified under the list of natural ports, and the pier is used to export and import petroleum derivatives, whether to global markets or to internal markets. The pier also stopped service completely during the month of November 2021 due to its lack of regular maintenance. The quantities of petroleum derivatives traded at the Brega Pier also witnessed fluctuating growth between increases and decreases, affected by the political and economic conditions that the country went through. The percentage of unloaded petroleum derivatives (imports) out of the total petroleum derivatives traded at the Brega Pier constituted the largest percentage during the year 2017 AD only, but during the years 2018 AD, In 2019 AD, 2020 AD, and 2021 AD, the percentage of shipped petroleum derivatives dominated the total petroleum derivatives traded on the dock, and the dock received only two types of petroleum derivatives: gasoline and diesel fuel, and shipped three types: heavy oil fuel, untreated naphtha, and kerosene fuel.